2012
DOI: 10.1111/j.1745-4549.2012.00795.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined Hurdle Effects of Process Parameters on Biochemical, Microbiological and Sensory Attributes of Trout Fillets

Abstract: The combined effect of brining time, citric acid, oregano oil and pasteurization temperature on the microbiological stability, pH, lipid oxidation (thiobarbituric acid reactive substance [TBARS]), total volatile basic nitrogen (TVBN) and sensory characteristics of trout fillets was evaluated. Sixteen treatment combinations were produced, packaged under modified atmosphere conditions and were studied for a period of 150 days. The total viable counts, phychrophiles, sulfite‐reducing clostridia and lactic acid ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
2
5
0
2
Order By: Relevance
“…Nevertheless, these differences can be considered of minimal interest taking into consideration the amounts of TVB‐N in freshly caught fish, which typically range between 100 and 200 mg N kg −1 . Similar to our findings, citric acid showed no effect on TVB‐N concentrations in trout fillets submitted to a brining process in which citric acid (1 g kg −1 ) or oregano oil (5 g kg −1 ) were added and subsequently packaged under a modified atmosphere and pasteurized …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Nevertheless, these differences can be considered of minimal interest taking into consideration the amounts of TVB‐N in freshly caught fish, which typically range between 100 and 200 mg N kg −1 . Similar to our findings, citric acid showed no effect on TVB‐N concentrations in trout fillets submitted to a brining process in which citric acid (1 g kg −1 ) or oregano oil (5 g kg −1 ) were added and subsequently packaged under a modified atmosphere and pasteurized …”
Section: Resultssupporting
confidence: 84%
“…reported that dipping of the fish in lemon juice before cooking vacuum packaged fish fillets had no effect on TBARS values after 42 days of refrigerated storage. Conversely, the addition of citric acid in soaking solutions/brines, icing mediums and chitosan coatings improved the oxidative stability of fish fillets …”
Section: Resultsmentioning
confidence: 99%
“…(2008) found pH values in fried, baked and microwave-cooked seabass at day 0 ranging from 6.69 to 6.73. However, Giavasis et al. (2012) found lower pH values in sous vide trout fillets with citric acid added.…”
Section: Resultsmentioning
confidence: 86%
“…(2004) obtained similar TVC counts for sous vide cooked rainbow trout after 14 days of storage at 2 ℃ with a similar heat treatment. Also, Giavasis et al. (2012) found TVC to be below the detection level for 150 days in sous vide trout cooked with sunflower oil, acid citric and oregano oil.…”
Section: Resultsmentioning
confidence: 97%
“…On the contrary, the antimicrobial effect and interaction of polyphenols and carvacrol were found to be more significant with the addition of acid which reduced pH (Giavasis et al . ). In the present study, polyphenols alone exerted a limited antimicrobial effect, while its combination with acid or carvacrol resulted in a higher antimicrobial activity.…”
Section: Resultsmentioning
confidence: 97%